2005
DOI: 10.13031/2013.20088
|View full text |Cite
|
Sign up to set email alerts
|

Role of Internal Nutrient Storage in Duckweed Growth for Swine Wastewater Treatment

Abstract: The objective of this study was to investigate the relationship of the nutrient content of duckweed biomass to duckweed growth in swine wastewater. Batch tests of Spirodela punctata 7776, the selected strain for highest total protein production, were conducted in an environment-controlled growth chamber at 24°C and 16 h of light per day. A prolonged growth period was observed after the nutrients in the medium were exhausted, indicating that duckweed could use its stored nutrients for growth. Prediction of grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Additionally, the influence of geographic isolate on the performance of duckweed in swine wastewater was more significant than that at the species level. A followup study was carried out to compare the performance of S. punctata 7776, L. gibba 8678 and L. minor 8627 in the reclamation of diluted anaerobically treated swine wastewater (67,50,33,25 and 20%) in a greenhouse [19]. It was reported that the Lemna geographic isolates produced more biomass and had higher content of tissue nutrients such as nitrogen, phosphorus and potassium than S. punctata 7776.…”
Section: Duckweed Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the influence of geographic isolate on the performance of duckweed in swine wastewater was more significant than that at the species level. A followup study was carried out to compare the performance of S. punctata 7776, L. gibba 8678 and L. minor 8627 in the reclamation of diluted anaerobically treated swine wastewater (67,50,33,25 and 20%) in a greenhouse [19]. It was reported that the Lemna geographic isolates produced more biomass and had higher content of tissue nutrients such as nitrogen, phosphorus and potassium than S. punctata 7776.…”
Section: Duckweed Strainmentioning
confidence: 99%
“…During the same nutrient starvation period, the duckweed biomass increased by 81.4%, resulting in a 220% increase in total starch. The continuous growth of duckweed in well water is believed to be supported by the internal nutrient storage of duckweed [67]. Assuming a corn starch yield of 5.70 t ha -1 year -1 [68,69], it takes only approximately 5 months to grow duckweed to reach the same starch yield per unit area.…”
Section: Cultivation Of High-starch Duckweedmentioning
confidence: 99%
“…Moreover, it grows faster and has a longer yearly production period than most other plants (Cheng and Stomp, 2009). In fact, many species of duckweed can double their biomass every 2e3 days (Chang et al, 1977), grow year-round in warm climates (Chaiprapat et al, 2005), and ultimately achieve a biomass of 0.5e1.5 metric tons/ hectare/day fresh weight or 13e38 metric tons/hectare/year dry weight (Skillicorn et al, 1993). In addition, duckweed has also been found to accumulate up to 75% of its dry weight as starch in optimal conditions (Reid and Bieleski, 1970), thereby making it an excellent feedstock for bioenergy production with ethanol yields of 6.42 Â 10 3 l ha…”
Section: Introductionmentioning
confidence: 99%
“…It has a longer production period than most other plants, even growing year-round in some areas with a warm climate [7]. It accumulates its biomass at more rapid rates than other higher plants, including agricultural crops [8].…”
Section: Introductionmentioning
confidence: 99%